The relationship between individual well-being, working environment and job satisfaction among factory workers in Malaysia - A. Manaf, Aini Maznina; Tengku Mohd Azzman, Tengku Siti Aisha; Buyong, Mazni; Syed Abdullah Idid, Syed Arabi (2018)
The present study examined the relationship between individual well-being, perceptions on the working environment and overall job satisfaction in the context of factory workers in Malaysia. A major purpose of the study is to identify main problems faced by factory workers in Malaysia. The study also aimed to examine the influence of demographic variables on job satisfaction, and the relationship between family income, individual well-being and perceptions on working environment, on overall job satisfaction among these factory workers. A survey was distributed among 551 factory workers working in the area of Klang Valley. Results indicate that two main problems faced by factory workers are fear with the influx of foreign workers that may threaten their job security, and the relatively low pay, considering that the high cost of living in Klang Valley. Findings also indicate that while gender and race did not significantly influence perceptions on working environment and job satisfaction, level of occupation did. Those working as security and logistic staff are significantly more satisfied with their working environment, compared to administrative or technical/production staff. Job satisfaction also varied significantly across level of occupation; those working in security and logistic positions were significantly satisfied with their jobs compared to other employees (administrative, managerial/professional, and technical/production). Finally, using a hierarchical linear regression, the findings suggest that after using family income as a control variable, individual well-being and perceptions on working environment both emerge as positive, significant predictors to perceived job satisfaction among factory workers. The implication of these findings will be discussed within the framework of Herzberg two-factor motivation theory.